Logic, Reasoning and Cognitive Sciences - Morales Delgado, Jorge (2024)
In our current work we analyze the various roles logic has had in the field of reasoning and human cognition mainly throughout the research program of cognitive sciences. We undertake the scrutiny of the three specific dimensions: (a) logic as a criterion, (b) logic as a model, and (c) logic as an approach. To address the above, we discuss several classical experiments and advances throughout the history of cognitive science, as well as some paradigms and approaches that have had a significant impact on logic and its methods.